Large-scale association analysis in Asians identifies new susceptibility loci for prostate cancer - Wang, Meilin (Nat Commun, 2015)
Genome-wide association studies (GWAS) have identified ∼100 genetic loci associated with prostate cancer risk. Less than a dozen of these loci were initially identified from GWAS in two Asian populations, likely because of smaller sample sizes of these individual GWAS in Asians. Here, we conduct a large-scale meta-analysis of two GWAS from the Japanese population (1,583 cases and 3,386 controls) and the Chinese population (1,417 cases and 1,008 controls), followed by replication in three independent sample sets. We identify two independent susceptibility loci for prostate cancer at 11p15.4 (rs12791447, P=3.59 × 10(−8); PPFIBP2) and 14q23.2 (rs58262369, P=6.05 × 10(−10); ESR2). The mRNA levels of PPFIBP2 and ESR2 are differentially expressed in prostate tumours and paired normal tissues. Our study adds two new loci to the limited number of prostate cancer risk-associated variants in Asians and provides important insight into potential biological mechanisms of prostate cancer.